ANALISA CYCLE TIME PADA PROSES CURING DI BAGIAN LINE 6 BIG DAN DENGAN METODE TIME STUDY PADA PT XYZ - Lokaputra, Riduwan; Rakawijaya, Febian; Gustawan, Gugi (Jurnal Sains Ilmu Teknologi Industri, 2023)
The existence of NVA activity can have an impact on high cycle time. In this case, PT XYZ has a problem where the cycle time exceeds the takt time, namely the curing process on line 6 of the Raw Edge Department. After observing the curing process, the highest cycle time was obtained, namely the joint leeve taking with a time of 231 seconds. In this process, there are activities that do not add value, such as searching and inspecting. This study aims to assist operators in retrieving, storing and reaching joint sleeves by making improvements such as classified shelves and ultrasonic measurement system. Before and after the repair, a time study was conducted to see the level of improvement based on production capacity and as a new standard for the curing process. Based on the results of research from improvements to the process resulted in the elimination of 2 elements of process work and inspection. There is an increase in production capacity of 2.58 slabs with a reduction in standard time of 175 seconds. This affects the cycle time of the curing process which was originally 845 seconds to 670 seconds.